The relationship between the field and the laboratory balance tests and skiing performance - Ruzic, L.; Petracic, T.; Radenovic, O. (Croatian Sports Medicine Journal, 2011)
Well developed proprioceptive abilities are the essential aspects of injury prevention and rehabilitation in many sports including alpine skiing. In our study we hypothesized that the field balance tests might be the factor that influences skier performance. The aim, therefore, was to determine which of the balance tests correlates most closely with skiing performance. The participants were 20 national alpine ski instructor candidates. The study design encompassed 3 simple laboratory balance tests (lateral and front-back tilts tests on the balance board, and hanging board balance test), 2 field balance tests (inner ski jump test and one leg carving test) and 3 official ski elements from Croatian Ski School (short slalom, giant slalom and off piste curves) that require high-level skiing skills. All elements were evaluated by three experienced independent judges. Multiple regression analysis singled out the inner ski jump balance test as the most important prediction factor for alpine skiing performance. We concluded that skiing coaches might find it useful to prescribe more field and specific balance training exercises to high level skiers, especially those which include inner ski jumps.